Pengaruh ruang terbuka aktif pada frontpage Gedung Sarinah terhadap aksesibilitas dan kenyamanan pejalan kaki - Akhsan Inant Tama Putra; Naniek Kohdrata (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Sarinah Building in Jakarta provides an active open space located at the building's frontage. This open space has a variety of activities and also the main access for pedestrian visitors. It might potentially have an impact on pedestrian accessibility and comfort when accessing the Sarinah Building. This research aims to formulate the relationship between pedestrian visitor behavior and the presence of open space on the frontage of the Sarinah Building. This research uses mixed method research with observation, survey, and literature review, where the results will be analyzed to understand the perceptions and behaviors of pedestrians. The result is open space at frontage positively impacts pedestrians with its continuity, proximity, spatial connectivity, readable, safety, cleanliness, green, attractiveness, and experiences. Apart from features and plants, various activities in open spaces are related to pedestrian behavior which makes it accessible and comfortable for pedestrians to access the Sarinah Building. This research can be used to consider the use of open space at the frontage as an active open space that makes accessible and comfortable for pedestrians.